Ca3Co4O9/polycrystalline Al2O3: an effective template for c-axis oriented layered cobaltate thin films by chemical solution deposition. Issue 23 (13th March 2015) - Wei, Renhuai; Tang, Xianwu; Yang, Jie; Dai, Jianming; Liang, Changhao; Song, Wenhai; Zhu, Xuebin; Sun, Yuping
<x xml:space="preserve">Abstract</x> Ca3Co4O9/polycrystalline Al2O3 thin film is an effective template for growth of c-axis oriented layered cobaltate thin films.